MEMBACA EMOSI KOMUNIKASI POLITIK JOKOWI DI INSTAGRAM - Silvanus Alvin (Ilmu Komunikasi, FISIP Universitas Pasundan, 2023)
The year 2022 places Indonesia as the international epicenter for hosting the G20 on 15-16 November. These crucial moments must be well-packaged and well-narrated to the media and the public. One approach taken by Jokowi is making the most of his Instagram, @jokowi. Every visual upload on social media has emotional content and can significantly influence the success of political communication. No research in Indonesia has been found examining emotions in political communication. A political actor communicates not only through visuals but also from the emotions emitted from the visuals. Emotions that are communicated can positively influence interested public or followers on social media. This research use content analysis. However, unlike the usual, this research will utilize cloud computing and machine learning platforms from Amazon Web Service (AWS), namely Amazon Rekogniton. In total, there is 98 visual information that will be analyzed using AWS. An interesting finding from this study is that Jokowi and the G20 guests mostly show happy and calm emotions.